PENGARUH ADAPTABILITAS KARIR TERHADAP KEPUASAN KERJA DENGAN OLDER WORKER AGE DAN MOTIVASI KERJA SEBAGAI PEMODERASI PADA PEGAWAI UNIVERSITAS SYIAH KUALA - M. Kardafi, Lenny Rakhmawati (Departemen Manajemen, 2017)
This study aims to determine the effect of career adaptability to job satisfaction with older worker age and motivation as a moderating. The empirical study conducted at Syiah Kuala University's staff used a questionnaire as a research instrument, which samples in this study of 120 people who are employees aged 40 to 60 years old. Probability sampling is used as a sampling technique with Simple Random Smpling. Methods MRA (Moderated Regression Analysis) is used as a method of data analysis using software IBM SPSS 20. These results indicate that the career adaptability positive and significant impact on job satisfaction, older worker age significantly and negatively related to job satisfaction, work motivation positive and significant impact on job satisfaction and in addition showed that the older worker age moderate positive effect on career adaptability to job satisfaction and motivation does not moderate influence on career adaptability to job satisfaction. Keywords : Career Adaptability, Older Worker Age, Work Motivation and Job Satisfaction.